Supersurfaces : folding as a method of generating forms for architecture, products and fashion. - Vyzoviti, Sophia, ....- (Amsterdam : Bis, 2006)
This booklet with the format of a pocket diary, makes clear how the new technique of folding can be applied not only in architecture, but also to industrial, product or textile manufacture. Vyzoviti uses paper as empirical model; she investigates and describes systematically how flat paper is transformed into volumes when creating prototypes. The research in this second book goes a step further using more durable materials than paper but with similar qualities. Supersurfaces is full of hand-folded, twisted, wound and woven forms. This 'other' manner of design is a 'low tech - high concept' morphogenetic process, which forms a welcome addition to common design methods with advanced computer programmes.
Keywords: Vouwconstructies